2019
DOI: 10.5114/kitp.2019.86361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetyl cysteine, vitamin E and vitamin C on liver glutathione levels following amiodarone treatment in rats

Abstract: Introduction Amiodarone, a pharmaceutical extensively used to suppress atrial and ventricular tachyarrhythmias, is also known to cause many side effects on many tissues. N-acetyl-cysteine (NAC), vitamin E and vitamin C are known as antioxidants for their ability to minimize oxidative stress. In the peer-reviewed literature, there is no study reporting on the protective effects of these antioxidant agents against its hepatotoxicity. Aim We investigated the oxidative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The main mechanisms in the development of DIFLD are thought to include lipogenesis and generation of free radicals leading to oxidative stress induction in hepatocytes. 44,75 Kim et al 76 showed that amiodarone caused an increase in short, medium-and long-chain acylcarnitines in the livers of rats, with the highest increases involving levels of acetylcarnitine. The most probable cause of these disturbances in liver tissue is the effect of amiodarone on mtFAO by blocking the activity of the carnitine palmitoyltransferase-1 enzyme, thereby directly inhibiting the mitochondrial β-oxidation of acyl-CoA to acetyl-CoA and by inhibiting complexes I and II of the MRC.…”
Section: Mechanisms Of Difld Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The main mechanisms in the development of DIFLD are thought to include lipogenesis and generation of free radicals leading to oxidative stress induction in hepatocytes. 44,75 Kim et al 76 showed that amiodarone caused an increase in short, medium-and long-chain acylcarnitines in the livers of rats, with the highest increases involving levels of acetylcarnitine. The most probable cause of these disturbances in liver tissue is the effect of amiodarone on mtFAO by blocking the activity of the carnitine palmitoyltransferase-1 enzyme, thereby directly inhibiting the mitochondrial β-oxidation of acyl-CoA to acetyl-CoA and by inhibiting complexes I and II of the MRC.…”
Section: Mechanisms Of Difld Developmentmentioning
confidence: 99%
“…Like amiodarone, it causes a reduction in liver glutathione levels, accumulation of oxidized form of glutathione, and lipid peroxidation. 75,81 Methotrexate and especially its polyglutamated metabolite are both stored in hepatocytes and exert hepatotoxic effects. 82 Several mechanisms are proposed for the hepatotoxic effect of methotrexate, including hampering of folate entry to mitochondria, which leads to mitochondrial dysfunction and generation of ROS and finally induction of caspase-dependent apoptosis.…”
Section: Mechanisms Of Difld Developmentmentioning
confidence: 99%
See 3 more Smart Citations